An improved method to evaluate indoor microclimatic data: case study of a book archive in a hot and humid climate - Ali, Maisarah; Oladokun, Majeed; Osman, Samsul Bahrin (2014)
Indoor microclimatic parameters are recurrently used to monitor building performance for indoor environmental quality appraisal. Inputs for such assessment come from time-series of microclimatic parameters taken with array of sensors and data loggers. Existing methods analyse the data using averages, cumulative frequencies, frequency distribution, standard deviation, ranges and other variability tests on the microclimate profiles to benchmark the results against existing standards. However, the approach is less efficient as only such variability tests are insufficient to report the microclimatic conditions. This study considers a different approach by comparison between standardised values of the raw data within similar time-step, at different data-points for in-depth analysis of indoor microclimatic parameters. The case study was selected of a book archive which conforms to ASHRAE standards on preservation with application of the current approach but reveals microclimate stratification as the proposed methodology is applied. This paper reports the approach, data collection, manipulation, analysis and presentation of the proposed method. Keywords: Indoor Microclimatic Parameters, Comfort Assessment, Indoor Air Quality, Time-Series Data, Hygrothermal Profile